90.1k views
0 votes
42 = -7 ( z-3)

whats z?

User Spencercw
by
5.6k points

2 Answers

5 votes

Answer and Step-by-step explanation:

We have to solve for z. That means everything that is next to z has to move to the other side of the equation.

First, divide -7 from both sides of the equation.

-6 = z - 3

Now add 3 to both sides of the equation.

-3 = z

z is equal to -3.

#teamtrees #PAW (Plant And Water)

I hope this helps!

User Israel Zinc
by
5.2k points
5 votes

Answer:

z = -3

Explanation:

42 = -7 ( z-3)

42 = -7z + 21

21 = -7z

z = -3

User Chiffa
by
5.1k points